Droplet Deformation and Oscillation in an Acoustic Levitator - Cai, Zixiu. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Douglas Matson.; Committee: Jannatun Nawer, and Glynn Holt.; Keyword: Mechanical engineering.